2016
DOI: 10.1088/0964-1726/25/3/035028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and magnetorheological study of 3-aminopropyltriethoxysilane-modified Fe3O4nanoparticles

Abstract: In this study, monodisperse Fe 3 O 4 nanoparticles were synthesized successfully using a sonochemical method in the presence of 3-aminopropyltriethoxysilane (APTES). The morphology, microstructure and magnetic properties of the bare Fe 3 O 4 and APTES-coated Fe 3 O 4 were investigated in detail by TEM, XRD, FTIR and SQUID. It was found that APTEScoated Fe 3 O 4 showed relatively gooddispersion with anarrow size distribution of 8.4±2.1 nmdiameter. The functionalization of Fe 3 O 4 was proved to be covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…In contrast, column structures formed have not been broken, or the new aggregates have been re-arranged, which indicates the presence of large CIPs in the MR fluid. Similar observations have been reported by other workers [44][45][46][47][48].…”
Section: Rheology Analysissupporting
confidence: 92%
“…In contrast, column structures formed have not been broken, or the new aggregates have been re-arranged, which indicates the presence of large CIPs in the MR fluid. Similar observations have been reported by other workers [44][45][46][47][48].…”
Section: Rheology Analysissupporting
confidence: 92%
“…2b may contain a stretching vibration of Fe-O-Si at 589 cm −1 overlaying with Fe-O vibrations from iron oxide 50 . The peak corresponding to Si-O-Si at 1015 cm −1 , and the bending and stretching vibrational modes of NH at 1637 cm −1 and 3400 cm −1 , respectively, confirm the coverage of silane with a free amine group of APTES on the MNS surface 58,59 . A band observed at 2920 cm −1 is due to C-H stretching vibrations of the anchored propyl group 60,61 .…”
Section: Resultsmentioning
confidence: 57%
“…Wang et al adopted the sonochemical method to prepare the APTES-coated Fe 3 O 4 NPs with diameter 8.4 ± 2.1 nm and concluded that the synthesized NPs exhibited superparamagnetism and good dispersibility. Magneto-rheological fluids prepared on the basis of these IONPs have typical magneto-rheological properties [ 192 ]. Li et al developed acetylated APTES-coated Fe 3 O 4 NPs based on the hydrothermal method.…”
Section: Surface Modification Of Magnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%